Towards a 15-minute city: redevelopment of Victoria Urban Terminal, Mauritius - Capery, Muhammad Shakeel; Kozlowski, Marek; Mohd Zairul (Human Resources Management Academic Research Society (HRMARS), 2024)
The "15-minute city" concept aims to create cities where all essential services and amenities are within a 15-minute walk, bike ride, or transit from residents' homes. It has gained popularity worldwide among urban planners and policymakers. The Victoria Urban Terminal in Port-Louis is a major transit hub connecting various neighborhoods and destinations. Its current design hinders accessibility by foot or bike from many parts of the city, making it incompatible with a 15-minute city concept. To address this issue, a gondola lift system is proposed as a fast, efficient, and sustainable transit option that can link the terminal to surrounding urban neighborhoods and amenities. This dissertation aims to explore the potential of implementing a gondola lift system at the Victoria Urban Terminal to support its redevelopment while aligning with the 15-minute city concept. It will analyze case studies, review relevant literature, and conduct interviews to gather information about the redevelopment of the existing terminal to adapt to a 15-minute city concept. The findings will contribute to the development of design guidelines for urban terminals in Mauritius, facilitating their integration into the 15-minute city framework.